TINJAUAN SEMIOTIKA NILAI AFEKSI DAN KESADARAN LINGKUNGAN HIDUP BERDASARKAN PERSPEKTIF FERDINAND DE SAUSSURE DALAM CERPEN ASAL-USUL POHON SALAK KARYA WILLY YANTO WIJAYA - Irfan Dany; Maman Suryaman (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
This article aims to semiotically review literary works, especially the short story Asal-Usul Pohon Salak by Willy Yanto Wijaya based on the perspective of Ferdinand de Saussure. A literary work, including a short story, in addition to having the physical and inner structure of the builder, also contains an element of implied meaning in the form of a certain symbolic language/sign. Semiotics studies is an approach/discipline of study that describes literary works based on the aspects of signs found/stated. Ferdinand de Saussure's theory is the preferred perspective for the study of semiotics in which there is an application of the principle of discussion of the main theory. There are a number of markers and markers that can be found in the fictional short story Asal-Usul Pohon Salak by Willy Yanto Wijaya. The results and discussions stated in this article are about signifiers and signified in the short story Asal-Usul Pohon Salak whose basis is the value of affection and environmental awareness built through excerpts of the text of the story.